The Relationship Between Fear, Loneliness, and Depression Among University Students: A Structural Equation Model - Abu Shind, Yousef Abdelqader; Al-Bahrani, Muna Abdullah; Alkharusi, Hussain Ali (COUNS-EDU: The International Journal of Counseling and Education, 2023)
The aim of this study was to test the causal relationship among fear of Covid-19, loneliness, and depression from Covid-19. The study sample consisted of 605 undergraduate students recruited from a public university. They completed three scales: fear of Covid-19, depression from Covid-19, and loneliness. The results revealed a good fit index for the proposed path model. The fear of Covid-19 predicted two types of loneliness emotional and social negatively. A positive association between depression and emotional as well as social loneliness was found. A total of 43% of the variance in depression was explained by loneliness.  Depression was potentially a mediating factor between a fear of pandemic and the feeling of loneliness. A counseling intervention can be designed based on these results.